O indianismo revisitado: A expedição Montaigne, de Antonio Callado - SILVA, Giselia Rodrigues Dias da (2011)
Since the Literature Training and Information until the contemporary literature, the Indian, under the most diverse shapes and shades, is always revisited by the Brazilian literary works. In this study, we observed how the novel A expedição Montaigne (1982), by Antonio Callado, incorporates in its narrative economy, the issue of indigenous peoples. This attempt to understand the approach of the Indian in a specific novel opened space for wider discussion. We seek, then, to understand what facets are coated the representation of the Indian in contemporary Brazilian novel, here understood as that novel produced from the second half of the twentieth century, supported mainly by reflections of Walnice Nogueira Galvão, who find themselves in a systematic test of the 1970, whose Indianism revisited" we took borrowed. Moreover, we discuss how the other novels, by Antonio Callado, produced during the same period, also deal with the issue of indigenous and, in parallel, pressing issues in a very specific moment in Brazilian history: the military dictatorship. To this end, we guided by our discussions in some studies critical of the singularities of the socio-historical, political and cultural Brazilian context of the second half of the twentieth century. As is the case of Tania Pellegrini, Regina Dalcastagné, Walnice Nogueira Galvão, and in the readings of novelist by Antonio Callado, whose main authors are Ligia Chiappini Moraes Leite, Alcmeno Bastos e Rejane Rocha. Thus, in an attempt to tie the threads, we finally reflect on how the narratological resources are mobilized in A expedição Montaigne to enable both a reassessment of the incongruities of the dictatorial regime that is already ending, as well as the historical and ideological contradictions that shape the representation of Indians in Brazilian novel.